Research Practices and Priorities of Chemistry Researchers in Western Himalayan Region of India - N, Muruli; Harinarayana, N. S. (DESIDOC Journal of Library & Information Technology, 2024)
The study aims to visualise the citation behaviour of Chemistry researchers in the Western Himalayan Region of India by analysing 16,823 sources cited in Scopus-indexed publications from 2012 to 2021. Employing the Bibliometrix and Biblioshiny packages within R Studio, the research delves into various bibliometric variables and keywords to present a detailed picture of Chemistry research. The study revealed significant insights into how Chemistry researchers in this region engage with the literature, predominantly relying on high-impact journal articles and reviews, with lesser emphasis on other document types. The visual analysis, including keyword occurrences and co-word network mappings, highlights prominent research themes such as ‘material synthesis and applications’ and ‘chemical and biological functions’. Additionally, visual tools like word clouds and tree-maps demonstrate the frequency and distribution of these keywords, emphasising the importance of interdisciplinary research that bridges Chemistry with fields like Biology, Materials Science, and Technology. The findings provide crucial information for stakeholders such as researchers, policymakers, and funding bodies, enabling them to grasp the research dynamics and priorities in the region.